A partition methodology to develop data flow dominated embedded systems - Esteves, António (2004)
Comunicação apresentada no International Workshop on Model-Based Methodologies for Pervasive and Embedded Software (MOMPES 2004), 1, Hamilton, Ontario, Canada, 15-18 June 2004.